The Formation of the Operating Interaction Mechanism of the Public and Corporate Finances in the Sphere of Social Service of the Population: Methodology, Theory and Practice - Karsakovich, Konstantin Aleksandrovich (International Journal of Economics and Financial Issues, 2016)
In this article the existing mechanism of cooperation between state and corporate finance in the field of social services are analyzed. The methodology of the formation of this mechanism, the legal aspects and the project approach are included. The factors that hinder the development of this mechanism are detected. They are: shortcoming of existing federal legislation; low wages and high load per social worker; outdated material and technical base of social service institutions; undeveloped market of social services. Also, the scheme to attract private investment in social services is formed based on Public-Private Partnership: concession agreement; long-term lease; personnel outsourcing or out staffing. Keywords: corporate and public finance, the mechanism of cooperation of finance, social services for the population JEL Classifications: H44, H42, M54.